Pemanfaatan Media Sosial Tiktok dalam Menarik Minat Pengunjung - Zahra Nabila Alfazriah; Anne Maryani (UNISBA Press, 2025)
Abstract. In the face of increasingly fierce competition in the tourism industry, the utilization of TikTok as a promotional platform becomes increasingly crucial. This research aims to explore the utilization of TikTok social media as a promotional tool in attracting visitors to Lembang Park Zoo. The research method employed is qualitative with a case study approach, involving direct observation, interviews, and document analysis. The research subject is promotional content published by the TikTok account @lembang_parkzoo. The informants in this study are the management of Lembang Park Zoo. Data analysis refers to Pierre Levy's new media theory and is conducted through data reduction, data display, and data verification stages, with attention to data validity through technical triangulation and observer triangulation. It is expected that the results of this research will provide valuable insights for Lembang Park Zoo managers and the tourism industry in designing more effective promotional strategies in the digital era. Abstrak. Menghadapi persaingan dalam industri pariwisata yang semakin ketat, penggunaan TikTok sebagai platform promosi menjadi semakin penting. Penelitian ini bertujuan untuk mengeksplorasi pemanfaatan media sosial TikTok sebagai alat promosi dalam menarik minat pengunjung Lembang Park Zoo. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus, melibatkan observasi langsung, wawancara, dan analisis dokumen. Subjek penelitian adalah konten promosi yang dipublikasikan oleh akun TikTok @lembang_parkzoo. Informan dalam penelitian ini adalah manajemen lembang park zoo. Analisis data ini merujuk pada teori new media oleh Pierre Levy dan dilakukan melalui tahap reduksi data, penyajian data, dan verifikasi data, dengan memperhatikan keabsahan data melalui triangulasi teknis dan triangulasi pengamat. Diharapkan hasil penelitian ini dapat memberikan wawasan yang berharga bagi pengelola Lembang Park Zoo dan industri pariwisata dalam merancang strategi promosi yang lebih efektif di era digital.